EVALUATION OF THE RELATIONSHIP BETWEEN CYTOKINE GENES AND HYPERLEUKOCYTOSIS IN ACUTE LEUKEMIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Objective. To study the relationship between the polymorphism of the gene IL17F (rs763780) and the development of hyperleukocytosis in acute leukemia. Methods. The material for clinical and laboratory studies in the work were patients with AL (n=102; ALL – 70 and AML - 32) who were admitted to the republican specialized scientific and practical medical Center of Hematology (RSSPMCH, Tashkent) from 2019 to 2023. Patients with AL were aged from 18 to 74 years, while the median age was 37.0±1.5 years. The diagnosis was established on the basis of diagnostic standards, taking into account clinical and laboratory data. The research methods included, in addition to clinical and laboratory (general blood test, myelogram), molecular biological research methods (detection of polymorphic gene IL17F (rs763780) by PCR in RT mode). The results were statistically processed using the PC application package “OpenEpi 2009, Version 2.3”. Conclusions. Weakened loci of the polymorphic gene IL17F (rs763780) (allele (Arg) - χ2=10.4; P=0.01 and genotype (His/Arg) - χ2=4.7; P=0.05) are significantly associated with hyperleukocytosis (>30 x 109/l) in AL.